PENGARUH TINGKAT PENDIDIKAN DAN PERAN ISTRI PETANI DALAM PENINGKATAN PENDAPATAN KELUARGA DI DESA DUMAGIN A KABUPATEN BOLAANG MONGONDOW SELATAN - Bansaleng, Yessikah Feiby; Paputungan, Hardiana F.; Panayi, Yunarsi; Gobel, Hasna Van (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
The urgency of this research is to determine the influence of the level of education and the role of farmer's wives on increasing family income in Dumagin A Village, South Bolaang Mongondow Regency, to increase understanding of the level of education, roles, ideas and contributions of farmer's wives in supporting family income and also to find out the conditions economics and understand the dual role of farmer's wives in depth because education is very important in creating an increase in family income. In this research, the influence of the level of education and the role of the wife is very important in creating changes to increase family income, so as to be able to solve problems related to Basic Research for Affirmation Beginner Lecturer researchers in the focus areas of Social Humanities, Education, Arts and Culture. The method in this research was carried out in several stages, totaling 4 (four) stages. The first stage is the preliminary study stage. At this preliminary study stage, the researcher made observations and looked for information related to the initial observation of the problem of education level and its relation to family income. The second stage, namely the data collection stage, was carried out by conducting interviews with respondents. The third stage is the data processing stage. In this stage the researcher processes data from interviews from respondents. The fourth stage is the conclusion stage. The data analysis technique used in this research is to analyze the level of education and the role of farmers' wives in increasing family income. The level of education greatly influences the role of farmers' wives in improving the family, both education levels from elementary school (SD), junior high school (SMP) and senior high school (SMA/SMK) even to undergraduate level (S1). The data obtained were analyzed without statistical tests by calculating the amount of money obtained from a farmer's wife's level of education and activities and the total income of the farmer's family multiplied by one hundred percent. Based on the results of research and discussion regarding the role of farmer's wives in increasing family income in Dumagin A Village, South Bolaang Mongondow Regency The following conclusion can be drawn: The influence of education level and the role of farmers' wives in increasing their household income in Dumagin A Village, South Bolaang Mongondow Regency has a very significant influence on family income. Either directly or indirectly. Based on research results, the level of education starts from elementary school, middle school, the role of the farmer's wife in Dumagin A Village, namely the economic role in the bureaucratic role, while the economic role is that the farmer's wife opens a stall and sells agricultural products. Meanwhile, the role in the bureaucracy is that the farmer's wife works as an ASN/Honorer. the income of farmers' wives is 19% with the average income of farmers' wives being IDR. 830,000 which is 19% of the entire workforce and education level.